16S rRNA sequence based identification of pathogenic gut microbiota of rohu Labeo rohita (Hamilton-Buchanan 1822) and silver carp Hypophthalmichthys molitrix (Valenciennes 1844) - Punom, Nusrat Jahan; Hasan, AKM Mahbub; Haque, Wahida; Begum, Mst Khadiza; Rahman, Mohammad Shamsur (Dhaka University Journal of Biological Sciences, 2016)
Rohu (Labeo rohita) and Silver carp (Hypophthalmichthys molitrix) are the most common, popular and commercially important fish of Bangladesh. Pathogenic gastrointestinal bacteria indicate the acceptability or quality hence it influences the economic status of these fish. To investigate the pathogenic gastrointestinal bacteria of these economically important fish of Bangladesh was carried out. Gut microbiota of indigenous Rohu and exotic Silver carp of three different markets of Dhaka metropolitan city were studied using various selective agar media, classical biochemical tests and 16S rRNA sequencing. Antibiotic susceptibility of selected isolates was also carried out against 14 antibiotics. Firstly, 216 colonies were differentiated morphologically and among them, 18 isolates were characterized by biochemical properties. Finally, the identification of 10 isolates were confirmed by sequencing the 16S rRNA gene. Total bacterial count (TBC), total Salmonella-Shigella and total Staphylococcal count exhibited significant difference (p < 0.05) between the species but not among markets. TBC of Rohu samples was 5.27 ± 2.01 × 107 cfu/g and in Silver carp was 3.02 ± 1.42 × 107 cfu/g, total Salmonella and Shigella was 6.94 ± 7.15 × 106 cfu/g from Rohu and 1.11 ± 0.97 × 106 cfu/g from Silver carp. Total Staphylococcal count was found 1.03 ± 0.52 × 107 cfu/g in Rohu and 5.48 ± 3.98 × 106 cfu/g in Silver carp. Biochemical assays provisionally determined 7 different bacterial genera from Rohu and 7 from Silver carp. Six different genera of Gram-negative bacteria (4 genera from Rohu and 2 from Silver carp) were identified as Aeromonas, Proteus, Pseudomonas, Enterobacter, Citrobacter, Klebsiella sp. by 16S rRNA sequencing. The results revealed that all the 18 representative isolates including reference strain (E. coli DH5α) were sensitive to ciprofloxacin and resistant to sulphamethoxazole. These findings might be due to the poor quality of the aqueous environment and reflects fish as the potential reservoir of pathogenic bacteria causing fish-borne disease outbreaks. Dhaka Univ. J. Biol. Sci. 25(2): 169-184, 2016 (July)